2001
DOI: 10.1046/j.1365-2133.2001.03951.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neuropeptide-degrading enzymes in alopecia areata: an immunohistochemical study

Abstract: These findings suggest that SP is endogenously released by dermal nerve fibres around hair follicles and that it may play an important part in epithelial-mesenchymal-neuroectodermal interactions in AA. This study reveals that SP and its degrading enzymes are involved in the pathogenesis of AA, which in turn might explain the pathological significance of neurogenic and psychogenic aspects in the disease process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 31 publications
1
58
0
Order By: Relevance
“…Recent evidence documented increased inflammatory infiltrate around the affected hair follicles in alopecia and the immune cells most significantly increased were the mast cells [17, 21, 23, 24, 25]; many of these were activated [17, 37]. Mast cell infiltration may be triggered by RANTES released from other immune cells [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence documented increased inflammatory infiltrate around the affected hair follicles in alopecia and the immune cells most significantly increased were the mast cells [17, 21, 23, 24, 25]; many of these were activated [17, 37]. Mast cell infiltration may be triggered by RANTES released from other immune cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…Murine skin mast cells were shown to be juxtaposed to nerve endings during hair follicle formation [40]and in alopecia, in which case the nerve endings were SP positive [37]. Mast cells, in turn, secrete vasoactive peptides and cytokines that contribute to the inflammatory content of the perifollicular area (fig.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine and tryptase act mainly on H 1 -receptor and proteinaseactivated receptor 2 (PAR 2 ), respectively. Numerous nerve fibres are present around the hair follicles in the scalp of patients with AA (6). It has been shown that histamine and PAR 2 agonist affect different neurones (7).…”
Section: Discussionmentioning
confidence: 99%
“…The number of SP-immunoreactive nerve fibers increase during early stage of AA, and decrease during advanced stage. SP and SP-degrading enzymes are highly expressed in the skin of AA-affected humans (Toyoda et al, 2001) and in the C3H/HeJ mouse model (Siebenhaar et al, 2007). AA onset may require stress-induced SP expression in the skin (Peters et al, 2006(Peters et al, , 2007.…”
Section: Stress-induced Perifollicular Neurogenic Inflammationmentioning
confidence: 99%